Two Reconstructions of Prehistoric Houses from Torun (Poland) - Grzegorz Osipowicz (EXARC, 2015)
In 1998 the Society for Experimental Primeval Archaeology (SEPA) was founded at the Institute of Archaeology at the Nicolaus Copernicus University (NCU) in Toruń. Since its beginnings, SEPA members have dedicated a great effort to engaging in numerous scientific experiments with the aim to present human lifestyle in prehistoric times in general. One of the indisputable successes of SEPA is the reconstruction of one of the supposed prehistoric birch tar and pitch production methods without the use of ceramics (Osipowicz 2005a), as well as the recreation of a Neolithic technique for making holes in stone axes (Osipowicz 2005b) and successful experiments with various techniques for bone and antler softening (Osipowicz 2007). At present, papers on the findings of further experiments in these fields are being prepared for publishing, as well as results of new experiments with use of, for example, ranged weapons, axes made of bone and antler and trampling. Moreover, the SEPA members also conduct wide-raging promoting activities by organising numerous archaeology fairs and presentations for schoolchildren.